Rheological Characterization of Mixed Aqueous Solutions of Enzymatic Hydrolysis Lignin and Ionic Liquid. Issue 21 (1st June 2022) - Ma, Yingchong; Zheng, Huanda; Zheng, Laijiu; Wei, Ligang; Cai, Tao; Zheng, Fuer
Abstract: Here we present a rheological study of enzymatic hydrolysis lignin (EH lignin) in 1‐butyl‐3‐methylimidazolium chloride ([C4 min]Cl) aqueous solutions. The effects of ionic liquid mass fraction, shear rate and temperature on the viscosity and macromolecular chain configuration of EH lignin / C4 min] Cl aqueous solution were studied. The results showed that the viscosity of the aqueous solutions increased with the increase of lignin content. The mass percentages of overlapping and winding, responding to divisions of lignin macromolecules existence state, were varied with changing in the temperature and mass percentages of ionic liquid. Increasing the mass of ionic liquid will significantly change the viscosity of lignin solution. Most of the lignin solutions had shear thinning behavior, suggesting that macromolecular chains of lignin moved with orientation to the fluid, and disentangled under the shear force. The viscosity of lignin solution decreased with the increase of temperature, and the viscosity activation energy increased with the increase of lignin or ionic liquid mass fraction. Abstract : At high concentration, the viscosity of EH lignin solution decreases with the increase of shear rate, showing pseudoplastic or shear thinning behavior within the tested shear rate range. This may be due to stronger entanglement between EH lignin chains at higher concentrations. With the increase of shear rate, the network structure is destroyed. Therefore, the corresponding shear thinning behavior was observed.